Pest categorisation of 'Blight and blight‐like' diseases of citrus. (11th April 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of 'Blight and blight‐like' for the EU territory. Blight is a major disease of citrus. Similar 'blight‐like' diseases are also known (e.g. declinio, declinamiento) and are addressed simultaneously with Blight in the present categorisation. The causal agent(s) remain(s) unknown and the potential role of a recently identified citrus endogenous pararetrovirus (Citrus Blight‐associated pararetrovirus, CBaPRV) remains to be established. Transmissibility and ability to produce consistent (although poorly specific) symptoms have been demonstrated and a combination of indirect approaches is used, with limits, for diagnosis. There are large uncertainties on the biology of the causal agent(s) and on the epidemiology of the disease, including the transmission mechanism(s) responsible for the observed field spread. Blight has been reported from North, Central and South America, Africa and Oceania but is not known to occur in the EU. It is listed in Annex IIA of Directive 2000/29EC. It has the potential to enter, establish and spread in the EU territory. The main entry pathway (citrus plants for planting) is closed by existing legislation and entry is only possible on minor pathways (such as illegal import). Blight is a severe disease and a negative impact is expected should it be introduced in the EU, but the magnitude of this negative impact is very difficult to estimate. 'Blight and blight like' satisfies all criteria evaluated by EFSA to qualify as a Union quarantine pest. It does not meet the criterion of being present in the EU to qualify as a Union regulated non‐quarantine pest (RNQP). Since the identity of the causal agent(s) of the Blight and blight‐like disease(s) and the existence and efficiency of natural spread mechanism(s) remain unknown, large uncertainties affect all aspects of the present pest categorisation.